Facilitators and Barriers to Implementing Sustainability in Oral Health Care - Catherine Minke Charlotte Volgenant; Sierou Bras; Ilona Francisca Persoon (Elsevier, 2022)
Objective: The aim of this research was to study the facilitators and barriers to implementation of sustainable oral health care in Dutch dental practices using a qualitative research design. Methods: A conceptual framework was developed and based on 2 theories for implementation in dental practices. The framework covered 4 levels: structural, dental practice, oral health care practitioner, and method and product level. Semi-structured interviews were conducted to collect guided and in-depth data. Fourteen key stakeholders were interviewed: dentists, dental hygienists, dental assistants, managers and owners of dental practices, and suppliers of dental goods. Data were analysed using both a thematic analysis approach and open coding. Results: Participants were aware of the compromised planetary health and, in part, of their contribution to it. However, turning this awareness into action proved to be challenging. Barriers that were identified included limited knowledge and awareness of the largest sources of planetary burden in oral health care. Also, information and availability of sustainable products and methods cannot yet meet the requirements of current performance standards, costs, and infection control guidelines. Facilitators that were observed included a growing awareness to contribute to planetary health and to implement sustainability outside oral health care, especially in women and younger people. Overviews and guides of existing sustainable methods are available, but additional methods and products should be developed as well. Conclusions: Many participants considered infection control guidelines as the most prominent barrier to sustainable oral health care. Women felt more involved with planetary health compared to men, which is in line with the concept of ecofeminism. It is essential for stakeholders to collaborate to reach the next levels of implementation. Action is required on all levels to secure both oral and planetary health. Now is the time to act.